ISAC: A Case Study of Systems Description Tools - Bødker, Susanne; Hammerskov, Jon (DAIMI Report Series, 1984)
ISAC is one of many methods for systems development. Such methods are developed in order to improve the quality and efficiency of systems development processes. Systems descriptions are made and used throughout the systems development process. The tools used for systems descriptions have an important impact on the quality of the descriptions which are produced and hence on the quality of the product of thesystems development process, the computer based system. This paper presents an analysis of the systems description tools used in ISAC by presenting some problems that occurred in an actual systems description process. The main problems are that ISAC imposes a structure on the systems descriptions which makes it impossible to describe important properties of information systems properly. Moreover, other important properties cannot be described at all. ISAC can only be used for sketching properties that are already familiar to the user, thus an ISAC description is insufficient as a means of communication within the systems development process.